Avaliação da ocorrência de ocistos de Cryptosporidium spp. e de cistos de Giardia ssp. e sua associação com indicadores bacteriológicos e turbidez na represa de Vargem das Flores - MG - Ana Maria Moreira Batista Lopes (2009)
This study was done at the dam of Vargem das Flores, a reservoir supplying the cities of Betim, Contagem and Belo Horizonte, (the three largest cities of Belo Horizonte Metropolitan Region, capital of Minas Gerais state). The dam is located in the dranage basin of ParaopebaRiver which belongs to the greater basin of Sao Francisco River. The choice of Vargem das Flores dam was due to its multiple uses, that is, public supply and recreation. The major objective was to characterize the occurrence of Cryptosporidium spp. oocysts and Giardia spp. cysts evaluating their association with the presence of both bacteria Escherichia coli and Enterococcus spp. and the turbidity in the Vargem das Flores reservoir. The monitoring program was from December/2007 to November/2008 and the sampling was carried out monthly. The four sites monitored were denominated station 1 (sampled in five depths) and 2, 3 and 4 (sampled in four depths each). The results indicate low concentrations of Cryptosporidium spp. and Giardia spp. (oo)cysts ranging from 0 to 4 oocysts/ 10 L and 0 to 8 cysts/10 L. However the occurrence of the protozoan was ubiquitous, offering danger to human health, if the water is consumed without previous treatment, like in recreational activities. The concentrations of E. coli ranged from <1 NMP/100 mL in all stations to > 2419.6 NMP/100 mL in the station 3. Similar to E. coli the highest values of turbidity were observed at station 3, which indicates a lower water quality. With regard to the Enterococcusspp. the minimum concentration was <1 NMP/100 mL also found in all stations and the maximum concentration occurred at station 2 (> 2419.6 NMP/100 mL) but no statistical differences were found among the stations. The stastical analyses results indicated poor correlation among protozoan, bacteria and turbidity. The stations 2 and 4 were framed in thecategory 2 of LT2, requesting therefore the removal of 1 additional log for systems with complete cycle, slow filtration or direct filtration. Moreover, the presence of animals around the reservoir shore enables the presence of protozoan in the water, offering a potential sanitaryrisk. The site used for water uptake was considered appropriate according to the protozoan values, once the distribution of the Cryptosporidium spp. and Giardia spp. (oo)cysts has not presented significant differences in any one of the monitored stations.